[Congenital toxoplasmosis: clinical manifestation, treatment and follow-up] [Article in Italian] • Il neonato con toxoplasmosi congenita: clinica, terapia e follow-up - Lina Bollani; Mauro Stronati (Hygeia Press di Corridori Marinella, 2014)
Toxoplamosis is a parasitic zoonosis which occurs worldwide, but is prevalent in Europe, South America and Africa. When infection occurs for the first time during pregnancy, mother to child transmission of the parasite can cause congenital toxoplasmosis. Rate of congenital infection ranges from less than 0.1 to approximately 1 per 1,000 live births. The risk of transmission depends on the gestational age at the time of maternal infection. A diagnosis of congenital toxoplasmosis is usually considered in infants who present: hydrocephalus, chorioretinitis, and intracranial calcifications, but this triade is very rare. Approximately 85% of the infants with congenital toxoplasmosis are clinically normal at birth; however, sequelae of infection may become apparent only months or even years later. Chorioretinitis is the main complication of congenital toxoplasmosis, late onset retinal lesions and relapse can appear many years after birth, but the overall ocular prognosis is satisfactory when infection is identified and treated accordingly. Fortunately, serious neonatal forms and severe neurological impairment have become rare, but prompt treatment of children with convulsions, abnormal muscle tone, hydrocephalus, may improve the prognosis and result in almost normal outcome. For infants who have congenital toxoplasmosis, treatment soon after birth for 1 year with pyrimetamine, sulfadiazine and leukoverin led to remarkable resolution of serious, active disease. A long follow-up is necessary to assess the long-term outcome of children and young adults with congenital toxoplasmosis, that is favourable for the majority of cases. Epidemiological surveillance needs to be improved in order to determine the effectiveness of prevention programs. Articoli Selezionati del "3° Convegno Pediatrico del Medio Campidano" · Guspini · 25 Maggio 2013 Guest Editor: Roberto Antonucci